An empirical evaluation of three post-Keynesian models - Peter Skott; Ben Zipperer (Intervention. European Journal of Economics and Economic Policies, 2012)
Structuralist and post-Keynesian models differ in their assumptions about firms' investment behavior and pricing/output decisions. This paper compares three benchmark models: Kaleckian, Robinsonian and Kaldorian. We analyze the implications of these models for the steady growth path and the cyclical properties of the economy, and evaluate the consistency of the theoretical predictions with empirical evidence for the US. Our regression results and the stylized cyclical pattern of key variables are consistent with the Kaldorian model. The Kaleckian investment function and the Robinsonian pricing behavior find no support in the data.Classification-JEL: E12, E32, O41
Keywords: 330; growth; business cycles; aggregate demand; instability; income distribution; utilization rate; investment function; pricing